Mass student sport in domestic and foreign practice - Vjаcheslav Shutieiev; Tetiana Shutieieva; Andriy Yefremenko; Olena Nasonkina; Mykhailo Marchenkov (Kharkiv State Academy of Physical Culture, 2017)
Purpose: carrying out of the comparative analysis of features of the organization of mass student's sports in domestic and foreign practice and their influence on the personality of students. Material & Methods: analysis of the special literature in which features of the organization of domestic and foreign mass student's sports are revealed. Result: currently in the development of student sports are two strategically different directions. One, based on the territory of the Soviet Union and which is being implemented in modern Ukraine, provides for students mandatory physical exercises in the educational discipline "Physical Education", as well as doing sports of their choice at leisure. The second direction, which is a consequence of the evolution of the Euro-American civilization, provides for the creation of conditions and opportunities for students to freely choose their types of motor activity, as a form of their leisure activities. Conclusion: conducted analysis testifies that in Ukraine in the student's environment there are four possible directions of the influence of sports on the formation of the personality of students: а) sports lessons for physical education in the educational process; b) sports sections; c) low cost sports clubs; d) sports clubs operating on a commercial basis. In foreign practice, the influence of sports on the formation of the personality of students is realized through various forms of club work.